Evaluation of the quality of business schools - confrontation of existing methodologies and stakeholders' views - Mykytyn, Pavel (2011)
This paper elaborates on the issues arising during evaluation of quality in tertiary education, specifically in the area of business schools. It provides an overview of theoretical approaches to quality and its measurement, and analyzes current methodologies in quality evaluation of business schools. Part of the thesis consists of results from an inquiry among academics from 4 departments of the Faculty of Business Administration at the University of Economics, Prague, and students of the CEMS International Management program. The results provide a comparison of current practices and stakeholder views, and shows whether these two are in alignment or contradiction.